filmov
tv
Prove that (1+cotA - cosecA) (1+ tanA +secA) =2, trigonometry, Class 10
Показать описание
Prove that (1+cotA - cosecA) (1+ tanA +secA) =2, trigonometry, Class 10
Maths With MADAN SHARMA
Рекомендации по теме
0:05:02
Prove that ( 1+ cotA - cosecA) ( 1+ tanA - secA) = 2
0:05:39
Prove that (1+cota-coseca)(1+tana+seca)=2. Prove that (1+cotθ-cosecθ)(1+tanθ+secθ)=2. #trigonometry...
0:06:49
Prove that (cotA/cosecA+1)+(cosecA+1/cotA=2secA
0:01:54
Prove that√((1+cosA)/(1-cosA))=cosecA+cotA
0:04:52
Prove: `(1+cotA-cos e c\ A)(1+tanA+secA)=2`
0:02:36
Prove that (CotA-CosA)/(CotA+CosA)= (CosecA-1)/(CosecA+1)
0:04:34
Prove: 1/((cotA)(secA)-cotA)-cosecA=cosecA-1/((cotA)(secA)+cotA)
0:08:02
Prove that: tanA/1-cotA + cotA/1-tanA = 1+secA.cosecA. | Class 10
0:03:22
Prove that sqrt{secA-1/secA+1} = cosecA - cotA #class10#icse#trigonometry#maths#inenglish#education
0:05:06
*Important question*|| Show that (1+cotA - cosecA) (1+tanA+secA)=2 || Maths Academy
0:01:51
Prove that (CotA + CosecA -1)/(CotA - CosecA +1) = (1 + CosA)/SinA
0:01:00
Prove: CotA+cosecA-1/cotA-cosecA+1 = 1+cosA/sinA Class10 Maths imp. Que. #shorts #youtubeshorts
0:10:13
Prove that (1+cota+tana)(sina-cosa)=seca/cosec^2a-coseca/sec^2a=sina.tana-cota.cosa | Trigonometry |
0:02:54
prove that cotA-cosA/cotA+cosA=cosecA-1/cosec+1
0:05:20
prove that tanA/(1-cotA) + cotA/(1-tanA) = 1+secA.cosecA
0:03:28
Prove that sinA(1+tanA)+cosA(1+cotA)=secA+cosecA
0:08:41
Prove cotA + cosecA - 1 / cotA - cosecA + 1 = 1 + cosA / sinA | Trigonometry | Mathematics class
0:05:19
1) Prove CotA +CosecA-1/CotA-CosecA+1=1+CosA/SinA in telugu || LAQS || Class 10 Trigonometry
0:02:53
Class 10- Trigonometric Identities-RD Sharma-Eg25,(ii), cotA+cosecA-1/cotA-cosecA+1=1+cosA/sinA
0:08:40
(1+tanA)² + (1+cotA)² = (secA + cosecA)² || Step by Step Proof|| Trigonometry
0:05:11
Prove that : (1+cotA-cosecA) (1+tanA+secA) =2
0:03:27
Evaluate (1 + TanA + SecA)(1 + CotA - CosecA). | Class 10 | Trigonometry |
0:00:51
prove (SinA/1-CosA)= (CosecA+CotA) | Class 10 NCERT Maths Trigonometry
0:07:18
Prove that (1 + cotA + tanA)(sinA - cosA) = (secA/cosec²A) - (cosecA/sec²A)